TRANSFORMASI PEMBELAJARAN PANCASILA MELALUI MODEL PANORAMA DAN MEDIA EDUCATION PLAY: PENINGKATAN DISIPLIN DAN CRITICAL THINKING SISWA SD - Hidayati, Ernita Rizka; Pratiwi, Diani Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the issue of students' low levels of discipline and critical thinking skills. These challenges stem from monotonous and unvaried teaching methods, along with minimal student engagement during the learning process. Furthermore, students often become easily bored due to the use of unattractive learning models and media. This research is a form of Classroom Action Research (CAR) aimed at analyzing the improvement of students' critical thinking skills and discipline. The results show a significant increase in student discipline, with the percentage of students categorized as "Highly Disciplined" rising from 26% in the first cycle to 95% by the fourth cycle. Likewise, students’ critical thinking skills improved from 32% to 95% in the "Highly Skilled" category. These findings indicate that the implementation of the PANORAMA learning model and the use of Education Play media were effective in enhancing both student discipline and critical thinking skills.